FAKTOR - FAKTOR YANG MEMPENGARUHI KEGIATAN ENTREPRENUERSHIP PADA IBU RUMAH TANGGA NELAYAN - Yohandes Rabiqy (JURNAL PERIKANAN TROPIS, 2017)
Marine resource is potential to improve the welfare of fisherman, but in the contrary the fisherman is still live under the poverty line. The study is aimed to analyse the economic activity of the fisherman’s wife using logit model including factors affecting income simultanously. Income significantly influenced by non fishing working hours and cost. While the fisherman’s income significantly influenced by working hours in fishing sector.